Reflexões sobre terminologia jurídica bilínque de contratos: subsídios para o tradutor de contratos em inglês - Ventura, Luis Henrique Pontes (2007)
When translating contracts from one language to another, translators are in the habit of excessively trusting in their intuition, which may lead them into error. This is because many are the false cognates, cases of polysemy and other aspects relating to problems that may cause confusion. Intending to avoid these mistakes, the majority of the translators who translate contracts usually use, as an aid to their task, bilingual law dictionaries, which present terms in an idiom, as well as their equivalent(s) in another language. However, the use of these terminological repertories does not keep the translator free from making mistakes when translating contracts. Focused on this situation we carried out a descriptive analytical study on part of the bilingual legal terminology, English-Portuguese and Portuguese-English, used in international contracts. In this way we identified and described units which within the contractual context acquire terminological value. This explains their affinity with other terms pertaining to the same system and where we have sought to resolve some of the problems relating to linguistic suitability faced by an international contract translator. As sources for our research we used legal books in the American English and Brazilian Portuguese languages, samples of acclaimed contracts in both languages, monolingual legal dictionaries, and with the purpose of confrontation, bilingual legal dictionaries. In this manner we raise legal terms used in contracts in general which could cause inappropriate translations and we present their respective equivalents in English and in Portuguese as a proposal. And finally, we compared the results obtained by us with the proposals of the main bilingual terminographic dictionaries in the area in question, so analyzing the efficiency of same. From this analysis it was possible to conclude that not even the intuition of the translator nor the bilingual legal dictionaries presently available are efficient instruments to the correct and efficient translation of contracts. This brings us to suggest that translators of contracts attempt to the contextual universe and that bilingual legal dictionaries be elaborated in a manner of presenting more complex information, as observations. As a suggestion, we proposed a prototype of bilingual legal dictionary, specialized in contractual terms, based in the reflections resulted from this research, which intends to present itself as a more efficient assistance to the translator of international contracts.